CLUSTER MANAGEMENT: FROM ECONOMIC AGGLOMERATION TO LEVERAGING INNOVATION - Tsakalerou, Maria Mariza (European Scientific Journal, ESJ, 2015)
Businesses clusters are defined as geographical concentrations of vertically and horizontally integrated firms in related lines of business. As such, clusters are complex and dynamic structures that are continuously evolving. Cluster management consists of the development of monitoring actions and interventions aiming to improve their capacities and capabilities. Strong clusters can promote economic growth by tapping into the unused business potential of a region. As the clustering effect evolves from mere economic agglomeration into an innovation agent, it is important to focus on ways to leverage this potential for development. The objective of this article is to provide a panorama of the issues and the challenges facing cluster management today.